2020
DOI: 10.3892/etm.2020.9505
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of CXCR3 and its ligands in spinal tuberculosis

Abstract: The present study aimed to investigate whether C-X-C motif chemokine receptor 3 (CXCR3) and its ligands may aid in diagnosing spinal tuberculosis (ST). A total of 36 patients with ST and 20 healthy controls were enrolled in the present study. The morphology of tuberculous granuloma in spinal tissue was observed by hematoxylin and eosin staining. The presence and distribution of acid-fast bacilli (AFB) were observed by Ziehl-Neelsen (ZN) staining. The protein expression of Ag85B, IFN-γ, and CXCR3 and its ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Our results demonstrated two main findings: (i) differential levels between groups (moderate increase in LTB, high in DS-TB, and extremely high in DR-TB) compared to HC and (ii) chemokines (CXCL10, CXCL9 and CXCL1) as the promising biomarker signature. These findings correlate with the previous postulations as both CXCL10 and CXCL9 and their elevated levels has been considered as potent diagnostic markers for both pulmonary and extrapulmonary TB 2 , 25 , 30 , 31 .…”
Section: Discussionsupporting
confidence: 90%
“…Our results demonstrated two main findings: (i) differential levels between groups (moderate increase in LTB, high in DS-TB, and extremely high in DR-TB) compared to HC and (ii) chemokines (CXCL10, CXCL9 and CXCL1) as the promising biomarker signature. These findings correlate with the previous postulations as both CXCL10 and CXCL9 and their elevated levels has been considered as potent diagnostic markers for both pulmonary and extrapulmonary TB 2 , 25 , 30 , 31 .…”
Section: Discussionsupporting
confidence: 90%
“…The interaction between CXCR3 and IP-10 may adversely affect T cell stimulation by APCs via disrupting the immune synapse formation [149]. Shang et al showed that the levels of CXCR3, IFN-γ and IP-10 in the blood of patients with spinal TB were significantly higher compared to those found in healthy subjects [150]. The results of Yu et al indicated that the expression of CXCR3 or CCR4 on CD4 + T cells might serve as a potential diagnostic marker in TB [151].…”
Section: Il-1 Receptor (Il-1r) Familymentioning
confidence: 99%
“…Tissue expression and blood levels of CXCR3 ligands have been evaluated in EPTB patients. One study showed that the expression levels of CXCR, IFN-γ, MIG, and IP-10 were increased and their blood concentrations were significantly higher in 36 patients with spinal TB than in healthy controls [36]. In addition, immunohistochemical analyses have demonstrated overexpression of MIG, IP-10, and I-TAC especially in granulomas in 26 patients with tubal TB, and their expression levels are correlated with disease severity [37].…”
Section: Discussionmentioning
confidence: 99%